Perkembangan Penelitian Hukum Pidana: Menyingkap Pola dan Dampaknya dalam Sistem Peradilan (Criminal Law) - Hudjolly; Ujang Badru Jaman; Yana Priyana (Westscience Press, 2023)
This research uses bibliometric analysis to explore the development of criminal law research, revealing patterns and impacts within the justice system. By analyzing scientific literature in this field, the research identifies main trends, influential authors, and emerging topics. The results of co-citation analysis, citation network analysis, and keyword analysis provide insights into the evolution of criminal law research. These findings enhance our understanding of this field, inform future research directions, and contribute to improving the justice system.